Pecuária em campo natural de dupla estrutura no bioma Pampa - Coelho, André Alfredo (2018)
The double structure grassland is an important food base for a cattle breeding in the state of Rio Grande do Sul. In this scenario, where the change and the change of structure, the investigation of patterns and processes of operation are fundamental to the management guidelines. Thus, we investigate the dynamics of the vegetation of a field of the physiographic region of the Southeastern Serra, submitted to continuous and rotational grazing. It was observed that management methods interfered in the composition of the forage mass without interfering without positive performance of the animals. In a compilation and adaptation of methods proposed to deduce the weight gain observed in rearing heifers, considering the verified vegetation dynamics. Logo of the middle of the project, understanding a proposal of a conceptual model for a minimal support solution in double structure fields. In addition, some impacts of rotational and continuous management on the vegetation state are oriented, suggesting that the lower management of the grazing process in the continuous control can lead the grassland to degradation states. However, the accumulation of biomass occurring in rotational grazing may not advocate increasing animal stocking without loss of ecosystem functionality. Having accumulated some information about the management of rural diversity, these are compiled in a closing chapter, with no intention of extending knowledge to practice. Finally, it was emphasized the importance of improving the minimum support model for double structure grassland.